Por que os empreendedores falham? uma análise sobre o comportamento empreendedor e a influência dos aspectos afetivos e cognitivos que impulsionam as falhas - Evangelista, Juliane da Costa (2022)
Most of the studies on entrepreneurs address the challenges and successes, seeking to offer an understanding of the potential of this social actor. There are few studies that focus on understanding the difficulties, pointing out the possible failures in the process of undertaking. Even scarcer are the studies that seek to understand failures from the perspective of psychological, affective and cognitive aspects. Concerns about these reflections led to the understanding of these phenomena and, thus, generated the following research problem: How does entrepreneurial behavior drive failures and are they more influenced by affective or cognitive aspects? Thus, this research aims to analyze how entrepreneurial behavior drives failures and whether they are more influenced by affective or cognitive aspects. The specific objectives were defined as follows: a) identify the types of failures that hinder the entrepreneur's actions in relation to the business; b) identify the behaviors that drive entrepreneurs to fail; c) to analyze whether entrepreneurs, when they fail, present behaviors more influenced by affective or cognitive aspects. The qualitative method of descriptive and exploratory nature was used and the data collection instrument was the interview, supported by a semi-structured script. Data were analyzed using content analysis (Bardin, 2011), whose results were categorized. As a main result, it is evident that behavior is influenced by affectivity and cognition, leading entrepreneurs to fail. The entrepreneurs' reports showed that affectivity and cognition act inseparably in this process, acting alternately, sometimes affective aspects interfere with cognition, sometimes cognition interferes with affective aspects. It is also noteworthy that in this process, when a certain affective or cognitive aspect acted in excess or in excess, it harmed the entrepreneur's behavior, driving failures. The purpose of this study was to bring contributions to debate about how the entrepreneur, when in a difficult moment, had his behaviors influenced by the affective and cognitive aspects and that led him to fail. In addition, the research made important contributions by identifying behaviors that resulted in damage to themselves and to the business.